Effect of Arthrodesis of the First-Metatarsophalangeal Joint on the Alignment and Stability of the First-Tarsometatarsal Joint: A Large Sample-Sized Radiographic Study - Yi Guo MD; Ankit Hirpara BS; Mingjie Zhu DAOM, MPH; Melissa L. Carpenter BS; Stephan Joseph MD; Donglai Huo PhD; Navsharan Singh BS; Edward Mardakhaev MD; Kenneth Hunt MD; Mark Myerson MD; Shuyuan Li MD, PhD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: The hallux metatarsophalangeal (MTP) joint plays an important role in maintaining mobility of the first ray and arthrodesis of this joint is used to treat a variety of deformities. Intuitively, fusion of a joint may cause instability of an adjacent joint, however, recent studies have shown that hallux MTP arthrodesis in patients with hallux valgus can improve the stability of the first-tarsometatarsal (TMT) joint. The goal of this study was to investigate the impacts of hallux MTP arthrodesis on the alignment of the first TMT joint in a large sample-sized cohort. Methods: This was a retrospective study that included one group of patients without hallux valgus (Control Group ) and one group with hallux valgus deformity. Pre-operative and six-month post-operative weight-bearing radiographs were used to evaluate the alignment of the hallux and the first TMT joint. The parameters included the hallux valgus angle (HVA), 1-2 intermetatarsal angle (IMA), first metatarsal–medial cuneiform angle (1MCA), medial cuneiform–first metatarsal angle (MC1A), relative cuneiform slope (RCS), and distal medial cuneiform angle (DMCA). A paired t-test was used to study the impact of first MTP arthrodesis on the above parameters, and an independent t-test was used to compare the difference of the surgical effect on those parameters between the two groups. Possible linear regression relationship was analyzed among those variants. Results: There were 32 patients in the control group (age 57.93 ±9.07) and 62 patients in hallux valgus group (age 65.26± 12.84). In control group, except for HVA, there was no change in any of the above parameters between the pre and post surgical images; while in hallux rigidus group, the HVA, IMA, 1MCA, MC1A, and RCS were significantly reduced after surgery (p < 0.05). The RCS increased slightly in control group, but decreased significantly in hallux rigidus group (p < 0.05). Between the two groups, there was a significant difference in the impact of surgery on HVA, IMA, MC1A and RCS. In hallux rigidus group, correlation detected between pre-post operative IMA with HVA and MC1A, HVA with 1MCA, 1MCA with RCS and DMCA, MC1A with RCS, RCS with DMCA. Conclusion: Hallux MTP arthrodesis improved the alignment of the first-TMT joint in patients with hallux valgus, but this change had no correlation with either the pre and postoperative IMA or HVA changes. There was no significant improvement nor worsening of the TMT alignment in patients without hallux valgus.